Merjenje moči stiska pesti G-judoistov - Pečnikar Oblak, Viktorija (Šport (Ljubljana), 2016)
More and more people with disabilities are choosing organized practice of judo, called G-judo. In addition to enhancing the physical body, socialization and well-being at practice is also important to them. The strength in hands is one of the key martial skills, so we decided to performed measurements of grip strength in G-judo group. Measurements were performed on a dynamometer Camry EH101 on a sample of 17 judokas 17 (4 girls in 13 boys) with special needs, where an average age was 20.82 (+-14.24) years, average height 160 (+-16.13) cm and average weight 60.66 (+-18.14) kg. Average belt level of the G-judo members was 7.65 (+-1.54) KYU. Measurements showed average grip strength of 21.3+-9.3 kg in the dominant side and 19.27+-7.83 kg in non-dominant side. A statistically significant difference between dominant and none-dominant hand was found t(14)=2.92, p = 0.011. In the process of data acquisition, it became clear that we can use hand dynamometer to determine the dominant hand of people with special needs, which can't or do not know how to write.
Keywords: dinamometrija; dynamometry; G-judo; judo; osebe s posebnimi potrebami; persons with disabilities; sport; šport